If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-10n+3(8+8n)=-2(n-4)
We simplify the equation to the form, which is simple to understand
-10n+3(8+8n)=-2(n-4)
Reorder the terms in parentheses
-10n+(+24+24n)=-2*(n-4)
Remove unnecessary parentheses
-10n+24+24n=-2+*(+n-4+)
Reorder the terms in parentheses
-10n+24+24n=+(-2n+8)
Remove unnecessary parentheses
-10n+24+24n=-2n+8
We move all terms containing n to the left and all other terms to the right.
-10n+24n+2n=+8-24
We simplify left and right side of the equation.
+16n=-16
We divide both sides of the equation by 16 to get n.
n=-1
| z+7=44 | | 8v+28=-3(v-2) | | 19-c=4 | | -7(k+3)-(-8k+7)=5 | | 2+3x-5x=-4 | | 16(x-9)=4(2a-x) | | -6(u+6)=4u+4 | | 1/4t+3/5=2/5-t | | -7x+3-5x=-57 | | 8+28m-24-12m=0 | | -34=5x+3(x+2) | | f(x)=a(x+3)(x+1)(x-4) | | 5y-7x=12 | | 6x^2+3xy+3y^2=108 | | x=-1.5+0.5y | | -3t^2+16t-11=0 | | 16x^2+64t+64=0 | | 6-2x(3-12)=2x+90 | | 20x+5=-2x | | 3(u-5)-6u=-33 | | 0.4-8.1y-2.7y=1-10.8y-0.6 | | 11(k-2)+[k-3(k+1)]=0 | | (3c-8)(3c-8)=0 | | y=-3+2y | | 7(y+2)-5y=-4 | | 8-28m-24-12m=0 | | 2(t-1)+3t=2 | | -2(d+6)=-20 | | 2*j=25+j | | K-(-40)=32 | | 2t-4=2 | | 36=4(8x+1) |